Oblikovanje poimenovanj za besedne vrste v slovensko pisanih slovnicah med leti 1791-1854 - Stramljič Breznik, Irena (Jezik in slovstvo, 1999)
A historical review of the formation of terms for word classes, based on word-formation analysis, shows that all those 19th century grammarians whose texts were analyzed, with the exception of Zagajšek, tended to create terms that would incorporate defining properties, of particular word classes. In 90 per cent of the cases, these terms were derived nouns, mostly with masculine suffixes. All these features make up the positive tradition upon which also contemporary linguistic terminology formation is founded
Keywords: Slovene; slovenščina; slovnice; grammar; besedne vrste; strokovna terminologija